KUANTIFIKASI DAN MITIGASI RISIKO PADA SISTEM RANTAI PASOK DI PT. ANEKA GAS INDUSTRI - Alfred Y. Tondatuon; Agung Sutrisno; Jefferson Mende (JURNAL POROS TEKNIK MESIN UNSRAT, 2013)
Effect and Analysis (FMEA) method, Risk Priority Number (RPN) Gas production need to consider the risks of the process of production and distribution. The purpose of this research is to identify the risks that exist in the supply chain management of PT. Aneka Gas Industri, and determine mitigation methods from any of existing risk. Identification method that used is the Failure Mode and Effect Analysis (FMEA), The FMEA tracking various types of failures from the existing system in PT. Aneka Gas Industri then analyze all the effects caused by the damage. The result that achieved is a descripton of the seriousness and consequences of risk for the company, and the quantification of the value of risk-based of Risk priority Number (RPN). The risk factors of power supply is the most part of critical failure with RPN score 729 and the risk factors of quality of the gas that’s uncertain will be a part of the lowest failure with RPN score of 18. Key words : Supply chain management, Failure Mode